The poetical theopedagogy of the wanderer of dialogue and hope called Paulo Freire (Revista Contexto & Educação, 2025)
This article intends to contribute with the memory of the life and work of Paulo Freire, as the Wanderer of Dialogue and Hope, celebrating its one-hundred-year anniversary. It intends to show how its Poetical Theopedagogy is lovingly libertarian and how its thoughts, its ideas and work, are actual and essential for the education and for all the society of our time. Making memory of the one hundred years of Paulo Freire is important, necessary, and always insufficient. The Recife-born master made himself an apprentice and learned with the simplicity and the wisdom of the farmers, among other workers for whom he taught through new methodologies the need of doing coherent options, of taking risks and of loving. Paulo Freire lives in its work that has the weight of an encyclopedia and the poetical beauty of a watercolor.
Keywords: Paulo Freire; Education; One hundred years; Memory; Freedom